PROSES PEMBELAJARAN GERAK DAN LAGU YANG KREATIF BERDASARKAN KURIKULUM 2013 DI TK MIRYAM SEMARANG (Jurnal Seni Tari, 2017)
This study aims to describe the learning process of motion and creative songs based on the Curriculum 2013 in Miryam Semarang Kindergarten. The method used in this research is descriptive qualitative research. The result of research is the learning process of motion and song covering the planning stage, implementation stage, and result. The planning stage consists of RPP. The implementation stage consists of opening activities, core activities, and closing activities. Result of this research is the students have participate in a intellectual and emotional learning procces, student have found learning concept and have responsibility to finishing task together.